2022
DOI: 10.3389/fphar.2022.872127
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol: A novel therapeutic agent for the inhibition of Candida species infection

Abstract: The high occurrence and mortality rates related to candidiasis emphasize the urgent need to introduce new therapeutic approaches to treat this infection. Eugenol, the main phenolic component of Clove and Cinnamomum essential oil, has been used to inhibit growth and different virulence factors of Candida, including strains with decreased susceptibility to antifungals, particularly fluconazole. The results showed that this compound could bind to Candida membrane and decrease ergosterol biosynthesis, consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Eugenol showed the lowest overall ΣFIC values when combined with miconazole (0.87) and nystatin (0.77), whilst α-pinene had the highest ΣFIC values of 2.13 (miconazole) and 1.73 (nystatin). Eugenol exhibited noteworthy antifungal activity against various fungal species due to its ability to damage the fungal cell envelope and attenuate virulence factors [ 74 ]. Several studies have demonstrated synergistic interactions between eugenol and various antifungal agents, including fluconazole, micafungin, and amphotericin B, against C. albicans and related species [ 75 , 76 , 77 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol showed the lowest overall ΣFIC values when combined with miconazole (0.87) and nystatin (0.77), whilst α-pinene had the highest ΣFIC values of 2.13 (miconazole) and 1.73 (nystatin). Eugenol exhibited noteworthy antifungal activity against various fungal species due to its ability to damage the fungal cell envelope and attenuate virulence factors [ 74 ]. Several studies have demonstrated synergistic interactions between eugenol and various antifungal agents, including fluconazole, micafungin, and amphotericin B, against C. albicans and related species [ 75 , 76 , 77 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, most of the interactions against C. albicans were non-interactive, which could be based on the fact that both the antifungal agent and the EOC may compete for the same molecular target [ 80 ]. Both nystatin and miconazole interact differently with the fungal cell membrane, which is also the primary molecular target for most EOCs [ 20 , 74 ]. Considering that EOCs can have multiple mechanisms of action which act sequentially and are not selective for a specific target site [ 48 , 80 , 81 ], the EOC may compete with the antifungal agent for the binding site and reduce the overall effectiveness of the combination.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin can bind to the ergosterol present in the membrane, which leads to fungal cell disruption and a loss of intracellular content [31]. Gallic acid and eugenol decreased the activity of sterol 14α demethylase P450 (CYP51) and squalene epoxidase, resulting in the inhibition of ergosterol biosynthesis [32,33]. Plumbagin disrupts the cell membrane integrity and reduces the metabolic activity of C. neoformans [15].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory growth activity was found to be mediated by causing membrane abnormalities, which include short, twisted hyphae and a reduction in conidia formation [175]. In another study, eugenol was reported to impart antifungal activity against C. albicans by inhibiting the synthesis of ergosterol, inducing oxidative stress, promoting lipid peroxidation, and increasing membrane permeability [176]. Similarly, eugenol displayed antifungal activity against clinical isolates of C. glabrata (MIC value: 128 µg/mL) by the inhibition of biofilm formation [177].…”
Section: Eugenolmentioning
confidence: 99%